Media narratives and linguistic agency: The role of language in framing perpetrators of violence against women and children in Indonesia - Harjanti , Fransisca Dwi; Ardiansyah, Roely (Universitas Ahmad Dahlan, 2025)
Language plays a crucial role in shaping public perception, especially in news reporting. This study examines how grammatical constructions are used to frame perpetrators of violence against women and children in Indonesian social media news. Using Critical Discourse Analysis (CDA), it focuses on four types of sentence structures—active voice, passive voice, nominalization, and subordinate clauses—to uncover how language influences the representation of agency and accountability. A total of 15 news articles published between 2023 and 2024 from seven online media outlets (Detik.com, BBC.com, Kompas.com, Liputan6.com, Sumbar.Suara.com, Kompas.com, and Andika TV) were analyzed qualitatively. The results show that passive constructions dominate, followed by active voice, subordinate clauses, and nominalization. Active sentences highlight perpetrators and institutional actions, while passive and nominalized constructions often obscure agency and shift attention toward victims or events. Subordinate clauses emphasize victims’ experiences, evoking empathy but weakening perceptions of offender responsibility. These linguistic patterns reveal how news discourse can influence emotional and moral judgments about gender-based violence. The findings emphasize the need for journalists to adopt clear, active, and ethical language use and for media educators to integrate discourse awareness into journalism training to promote responsible and balanced reporting.